Factor that contributes towards declination of sales and demand in inspection services: case study of SGS (M) Sdn Bhd / Isma Faishal Amir Mohd Zamzuri - Mohd Zamzuri, Isma Faishal Amir (2017)
Inspection is the process of measuring the qualities of a product or services in terms of established standards. Whenever products are manufactured some of them may be in the limits of error and some may be outside. The allowances provided with the help of inspection on such products are selected which satisfy the conditions ot work. Thus inspection n is an important aspect of production control. The purpose of study is to identify the factor that contributes towards the declination of sales and demand in inspection services. The issue that arises in this study are price, technology, and economy. 100 customers had been selected as respondents due to the constraint time and willingness of respondents to reply correctly and willingly, By using judgment sampling, the questionnaires are distributed to client of SGS. Therefore, throughout the research findings, there's only one hypothesis were support the research. Overall. price is the dominant factor that contributes towards the declination of sales and demand in inspection services.